Wyrok Sądu Najwyższego z dnia 28 maja 2014 roku, I CSK 330/13 - Redakcja PPPM (Problemy Prawa Prywatnego Międzynarodowego, 2015)
This gloss concerns a Supreme Court ruling on establishing separate marital property for spouses living in Poland and France. The SC considered Polish courts' jurisdiction based on the Polish-French agreement. The husband's cassation appeal, seeking an earlier separation date based on a French court's interim order, was dismissed. The SC found the French order wasn't equivalent to Polish legal separation and didn't automatically trigger property division.